Chapter 9 Awkward Connections Stand-Up Comedy as Affective Arrangement - Lindfors, Antti (Taylor & Francis, 2023)
This chapter explores stand-up as an affective arrangement, i.e., as goal-driven phatic labor that rests on forging and manipulating affective relations - connection for short - between performer and audience. Drawing on linguistic/semiotic anthropological work on phaticity as well as feminist work on affect, it attends to the manner in which this affective and connective dynamic is discursively formulated amongst practitioners and naturalized into an array of tropes and metaphors that construe stand-up as a self-regulating autopoetic organism and atmospheric field of energies, pressures, and intensities. Moreover, the chapter unveils the prospective communicative and connective gap of awkwardness as something endemic to the social and political dynamic of stand-up.